2017
DOI: 10.5400/jts.2017.v22i3.183-189
|View full text |Cite
|
Sign up to set email alerts
|

Population and Diversity of Arbuscular Mycorrhiza Fungi in the Rhizosphere of Kasetsart Cassava Clone Grown on Two Different Locations

Abstract: ABSTRAKPopulation and diversity of arbuscular mycorrhiza fungi (AMF) are varied in the soil and influenced by biotic factors such as host plant and abiotic factors such as soil fertility, soil moisture, pH, temperature, etc. This study aimed to determine the population, diversity, and the dominant type of AMF in the rhizosphere of Kasetsart cassava clones obtained from LampungTimur and Tulang Bawang Barat Regencies, Lampung Province, Indonesia. Population of AMF was counted directly from the rhizosphere of Kas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Oil palm is a symbiotic plant with AMF, either naturally [12,13] or intentionally applied with exogenous AMF [14,15]. In nature, AMF populations are strongly influenced by vegetation and abiotic conditions of the soil [6,8]. Based on the results of this study, it can be seen that the highest AMF spore population in the oil palm rhizosphere inside the circle was obtained from Paleudults mineral soils, followed by peat soils (Haplosaprists) and mineral soil Dystrudepts, while the lowest from soils sandy soil Haplohumods (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Oil palm is a symbiotic plant with AMF, either naturally [12,13] or intentionally applied with exogenous AMF [14,15]. In nature, AMF populations are strongly influenced by vegetation and abiotic conditions of the soil [6,8]. Based on the results of this study, it can be seen that the highest AMF spore population in the oil palm rhizosphere inside the circle was obtained from Paleudults mineral soils, followed by peat soils (Haplosaprists) and mineral soil Dystrudepts, while the lowest from soils sandy soil Haplohumods (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The chemical properties of this peat soil are better than mineral soil, but the number of spores in the oil palm rhizosphere in this soil is lower than that of Paleudults soil. The high content of organic C in the soil is thought to be a factor limiting the development of mycorrhizae in the Haplosaprists soil [6]. reported that the number of AMF spores was higher in cassava fields containing higher organic C of 1,42% when compared to low organic C of 0,78%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations